2020
DOI: 10.1097/nmd.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Single-Session Dance/Movement Therapy for Thought and Behavioral Dysfunction Associated With Schizophrenia

Abstract: This purposes of this mixed methods feasibility study were to determine whether people with schizophrenia in an inpatient psychiatric facility were able to complete the research protocol, and to obtain preliminary treatment effects of a single-session dance/movement therapy (DMT) intervention versus verbal treatment as usual (TAU). Thirty-two participants were randomized to a 45-minute DMT or verbal TAU session. Data were collected quantitatively using the Brief Psychiatric Rating Scale (BPRS) and qualitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…This is particularly pertinent based on the aforementioned stigmatization people with schizophrenia are faced with, contributing to disrupted interpersonal relationships. Both Biondo et al (2021) and Bryl et al (2020) reported an increase in self-awareness inclusive of mind-body awareness in these studies. Bryl et al (2020) conducted a mixed methods randomized controlled trial (N = 31) providing 20 group DMT sessions over 10 weeks.…”
Section: Dance/movement Therapy and Schizophreniamentioning
confidence: 68%
See 4 more Smart Citations
“…This is particularly pertinent based on the aforementioned stigmatization people with schizophrenia are faced with, contributing to disrupted interpersonal relationships. Both Biondo et al (2021) and Bryl et al (2020) reported an increase in self-awareness inclusive of mind-body awareness in these studies. Bryl et al (2020) conducted a mixed methods randomized controlled trial (N = 31) providing 20 group DMT sessions over 10 weeks.…”
Section: Dance/movement Therapy and Schizophreniamentioning
confidence: 68%
“…Moreover, the nonverbal relationships possible through DMT can allow for increased joining and attuning with those who may have communication differences. These components of invitation for people with schizophrenia truly meet each participant where they are in their wellness process and destigmatize the diagnosis, allowing an authentic development of healthy ego, self-efficacy, and relationship (Biondo et al, 2021;Bryl & Biondo, 2022). This review seeks to highlight the disparities people with schizophrenia face regarding lack of accessible (Swildens et al, 2016) and quality health care (Moore et al, 2015;Sølvhøj et al, 2021), multifaceted forms of stigmatization they encounter (Ivanova, 2021;Kohn et al, 2022;Sølvhøj et al, 2021), and specific barriers they face regarding the bodily disruptions and dysregulations associated with their symptomatology (Biondo et al, 2021;Costantini et al, 2020;Torregrossa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations